PENGARUH PENANAMAN MODAL DALAM NEGERI, TINGKAT PENGANGGURAN TERBUKA, ANGKA PARTISIPASI SEKOLAH TERHADAP KEMISKINAN MULTIDIMENSI DI SUMBAGSEL DALAM PERSEFEKTIF EKONOMI ISLAM (ANALISIS DATA PANEL TAHUN 2019-2023) - Komaria, Desi; Fasa , Muhammad Iqbal; Kurniawan, Agus (Bussman Journal : Indonesian Journal of Business and Management, 2025)
This proposal examines the impact of domestic investment and other factors such as open unemployment rates and school enrollment rates on multidimensional poverty in the Southern Sumatra (Sumbagsel) region. Furthermore, this study integrates an Islamic economic perspective in poverty alleviation, emphasizing the role of zakat, infaq, and waqf as effective instruments of social and economic empowerment. The quantitative approach uses panel data and statistical analysis to measure the influence of independent variables on multidimensional poverty levels, and discusses the theoretical and practical benefits of this research for the development of sustainable and inclusive economic policies. Thus, the results of this study are expected to provide strategic recommendations in order to reduce poverty structurally and multidimensionally, and support equitable and competitive economic development in Indonesia, especially in the Sumbagsel region.